War, Crime and Disease: An Evaluation of the Double Threat of Terrorism (Groundings Undergraduate, 2016)
Since 9/11 and the declaration of the War on Terror, terrorism has featured prominently in the 21st century security agenda. As a result, a wide range of counterterrorist measures have been developed in order to provide security in states across the globe. Yet their intensification, while ostensibly diminishing one threat, has arguably increased the threat to another: civil liberties. By adopting Sederberg’s typology of counterterrorist measures into war, crime and disease approaches, the following analysis seeks to determine the degree to which they alter the balance between security and liberty. Drawing upon evidence from counterterrorist strategies in the US, UK, EU, France and Norway, this article demonstrates that liberal democracies should refrain from securitising or de-politicising terrorism, as either approach would come at a cost to liberty and security, respectively. Rather, the politicisation of counterterrorism, found particularly within the crime approach, offers the most practicable balancing solution to the ‘double threat’ of terrorism.
Keywords: Terrorism; Security; Civil liberties; Counterterrorism; Sederberg; War; Crime; Disease; Liberty